Risk factors for repeated cholera outbreak in Arua munic ipal council, north-western Uganda - Andrawa, M.; Anguzu, P.; Anguaku, A.; Nalwadda, C.; Namusisi, O.; Tweheyo, R. (International Journal of Infectious Diseases, 2010)
Cholera outbreaks have occurred annually in Arua district especially in the Municipal Council (AMC) since 2005 with an average case-fatality rate (CFR) of 2.1%. The study objective was to establish the risk factors for repeated cholera outbreak in AMC with a view of designing appropriated strategies for preventing future cholera outbreaks.
Keywords: Cholera outbreak; Risk factors